2010
DOI: 10.1007/s00464-010-1307-4
|View full text |Cite
|
Sign up to set email alerts
|

Suprapubic single-incision laparoscopic appendectomy: a nonvisible-scar surgical option

Abstract: Suprapubic SILS appendectomy offers better, cosmetically appealing results than the standard umbilical access. In case of retrocecal or purulent or gangrenous acute appendicitis, the view provided via the suprapubic approach makes access to and dissection of the appendix easy, and it also enables exteriorization of a drain without adding new lateral incisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 14 publications
0
27
0
2
Order By: Relevance
“…All studies reported a single skin incision through the umbilicus except four, [1][2][3][4] in which surgeons performed an infraumbilical incision. The literature broadly describes three approaches to SPILA referred to throughout this review as: > SPILA unassisted: any procedure using specialised or conventional laparoscopic instruments through a single skin incision in the abdominal wall, regardless of the number of fascial incisions > SPILA assisted: as SPILA with the additional use of percutaneous sutures or wires to 'assist' the operation > Hybrid: any procedure in which the appendix was exteriorised using a single incision, laparoscopically assisted operation but divided subsequently using a conventional 'open' appendicectomy technique…”
Section: Surgical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies reported a single skin incision through the umbilicus except four, [1][2][3][4] in which surgeons performed an infraumbilical incision. The literature broadly describes three approaches to SPILA referred to throughout this review as: > SPILA unassisted: any procedure using specialised or conventional laparoscopic instruments through a single skin incision in the abdominal wall, regardless of the number of fascial incisions > SPILA assisted: as SPILA with the additional use of percutaneous sutures or wires to 'assist' the operation > Hybrid: any procedure in which the appendix was exteriorised using a single incision, laparoscopically assisted operation but divided subsequently using a conventional 'open' appendicectomy technique…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Twenty studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] including 584 patients met the definition criteria for 'SPILA unassisted' approaches. The use of special multi-conduit ports was reported in four studies [4][5][6][7] ( Fig 1).…”
Section: Spila Unassistedmentioning
confidence: 99%
“…4,[12][13][14][15][16][17][18] But the successive rate of SILS technique can be confirmed by prospective clinical trial but no study was found yet.…”
Section: Discussionmentioning
confidence: 98%
“…4 Although claims of enhanced recovery and pain as well as blood loss and complication reduction as compared with conventional laparoscopic and open procedures have yet to be proved demonstrably, single port/incision laparoscopic procedures are increasingly being performed. [5][6][7] Reduced scarring is the most evident advantage of single incision laproscopic surgery (SILS). Optimal cosmetic results are obtained through intraumbilical incision as the scar will be concealed within the umbilicus but a major concern may be injury to the epigastric vessels.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Various methods have been reported, from a single incision at the right iliac fossa 12 to use of a single suprapubic incision that can be concealed in the pubic hair. 13 Among these methods, a single incision at the umbilicus is virtually scarless. Since 1992, after the initial performance of a single-trocar appendectomy by Pelosi various studies evaluating transumbilical single incision laparoscopic appendectomies have been conducted.…”
Section: Introductionmentioning
confidence: 99%